MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BAHASA INDONESIA MELALUI PEMBELAJARAN BERBASIS LINGKUNGAN PADA PESERTA DIDIK KELAS VII – 4 SMP NEGERI 8 GORONTALO - Hasna Isa (Kantor Bahasa Provinsi Gorontalo, 2017)
This research aimed to increase the result study of the students throuhgenvironment based learning. Implementation obsevation action classconsisted of two cycles. Procedure implementation observation action class 4 steps such as: (a) preparation action, (b) implementation action, (c) monitoring and evaluation, (d) analysis and reflection. The result ofimplementation observation action class axplanation as; in the first cycles implementation action reach out 70 % and the result studyng reach out 75,6 % or 25 students had complete. In the second cycles implementation action reached out 87.5 % and the result studyng 87,9 % or 28 students had complete.From the result inmplementation observation action class, it can beconcluded that assembling studying based of environment increases theresult studying students in Bahasa Indonesia.